A Study of Demographic Variables Affecting Consumer Buying Behaviour with Reference to Synthetic Detergents - Chatterjee, Sebabrata (Indian Journal of Marketing, 2013)
The research attempts to study the consumer buying behaviour of synthetic detergents in an Indian setting, specifically with reference to southern West Bengal. In this paper, the impact of a few demographic variables on consumer buying pattern has been established. A few non - demographic variables have also been considered to test the association between demographic and non-demographic variables which are involved in consumer buying behaviour of synthetic detergents. The study was conducted in both urban and sub-urban areas of southern West Bengal during the time period from 2011-2012. Results indicate that there is an association / relationship between the demographic variables and non-demographic variables of the consumers, and the FMCG companies in India should pay more attention towards the demographic characteristics of their target consumers. Demography has traditionally helped the marketers to evolve positioning strategies and people having common demographic characteristics behave in an identical manner and will have the same preferences. This study also attempts to contribute to the knowledge of how FMCG companies will be able to understand the buying preferences of the consumers.